Taqwīmu Ta’līm Al-Lughah Al-‘Arabiyyah ‘inda Imām Zarkasyi wa Imām Syubbāni fī Kitāb Al-Tamrīnāt - Rizza Faesal Awaludin (Study Program of Arabic Language Teaching, 2020)
The evaluation book has been made a lot during this time, and one of the books that is carried out in the evaluation in teaching Arabic is the book “At Tamrinaat” as an application of the book “Durūsul Lughah Al Arabiyyah” written by KH. Imam Zarkasyi and Imam Syubani. Teaching Arabic in the words of KH. Imam Zarkasyi and Imam Syubani is in the book